Grounds, Procedure, Legal Consequences of the Abolition of Adoption - E. G. Beglyarova (Сибирское юридическое обозрение, 2023)
The topical issues that arise when considering civil cases on the abolition of adoption, priority areas for protecting the rights and legitimate interests of minors are investigated. Children left without parental care are by far the most vulnerable socially and morally. The article presents a comprehensive view of this issue from both legal and psychological points of view. On the legal side, it is indicated that it is possible to transform a number of legal norms enshrined in the Family Code of the Russian Federation in order to apply them most effectively. From the psychological point of view, the necessity of mandatory use of special psychological knowledge in resolving disputes in this category is determined. In addition, the special role of the prosecutor and the guardianship and guardianship authorities in the judicial process in cases related to the abolition of the adoption of a child is described. Particular attention is directed to the fact that the adoption of a decision to cancel the adoption should primarily meet the interests of minors, contain an unconditional character. The corresponding consequences of the decisions made by the court to cancel the adoption are given. The object of the study is the totality of social relations that arise during the consideration of civil cases of this category. The subject is the norms of civil, family and civil procedural law governing the above relations, the system of their implementation and application. Judicial acts are analyzed: decisions (determinations) of courts to cancel adoption, statistical and reporting data are summarized, grounds for filing claims are determined. Aspects related to the need to apply preventive measures aimed at excluding formal grounds for filing applications for the cancellation of the adoption of children are highlighted. Emphasis is placed on the participation in the consideration of disputes of this category of specialized entities, endowed with appropriate powers and having special knowledge in the field of psychology, sociology, and pedagogy. Based on the results of the study, the author formulated certain conclusions, made practical proposals for a more effective application of the norms of the current legislation, primarily in order to respect the rights and interests of children. Certain options for adjusting a number of norms of the current legislation in this area are proposed.